An Act Defining Crime and Punishments, 130, Ch. 49, Sec. 72, in Revised Statutes of the Territory of Iowa (Reprint 1911) - (:unkn) unknown (My University, 1843)
Prohibited aiding prisoners in jail from escaping by, among other methods, conveying instruments or arms. Violators fined not less than one hundred nor more than five hundred dollars and imprisoned in the penitentiary at hard labor for a term not exceeding two years.
Keywords: TRANSFER - DANGEROUS PERSONS